(untitled) (Cincinnati, Ohio, 1998)
Text covers the field as accessibly and concisely as possible, in a way that emphasizes the relevance of macroeconomics's classical roots and its current practice. Featuring the latest data, new case studies focused on recent events, and a number of significant content updates.
Keywords: Macroeconomics,Kinh tế vĩ mô